Multiple β-Lactam Resistance Gene-Carrying Plasmid Harbored by Klebsiella quasipneumoniae Isolated from Urban Sewage in Japan - Yasunori Suzuki (American Society for Microbiology, 2019)
ABSTRACT The continuous emergence of carbapenemase-producing Enterobacteriaceae (CPE) presents a great public health challenge. Mitigation of CPE spread in the environment is crucial, particularly from a One Health perspective. Here we describe the isolation of CPE strain SNI47 from influent water of a sewage treatment plant in Japan. SNI47 was identified as Klebsiella quasipneumoniae subsp. quasipneumoniae by phylogenetic analysis and was resistant to β-lactams, including carbapenems. Of four plasmids detected from SNI47, the 185,311-bp IncA/C2 plasmid (pTMSNI47-1), which carried 10 drug resistance genes, including genes for four β-lactamases (blaCTX-M-2, blaDHA-1, blaKHM-1, and blaOXA-10), was transferred to Escherichia coli J53 via conjugation. The MICs of all tested β-lactams for the transconjugant were higher than for the recipient. We constructed recombinant plasmids, into which each β-lactamase gene was inserted, and used them to transform E. coli DH5α cells, demonstrating that KHM-1 enhanced carbapenem resistance. In addition, these β-lactamases were responsible for a wide-spectrum β-lactam resistance acquisition with mutual compensation. KHM-1, recognized as a rare type of metallo-β-lactamase, was detected in a transferable plasmid, from a sewage treatment plant, involved in horizontal gene transfer. The detection of such plasmids raises a health risk alarm for CPE dissemination. IMPORTANCE In our investigation of urban wastewater in Japan, carbapenem-resistant Klebsiella quasipneumoniae subsp. quasipneumoniae was isolated that carried the pTMSNI47-1 plasmid, which carries four β-lactamase genes and has transferability among Enterobacteriaceae. pTMSNI47-1 was found to encode a rarely reported carbapenemase, KHM-1. Cooperative effects of β-lactamases encoded by pTMSNI47-1 appeared to have broad-spectrum resistance to β-lactams. The detection of the KHM-1 gene in urban wastewater suggests that such a rare antimicrobial resistance (AMR) gene can be pooled in the environment, potentially emerging as an AMR determinant in a pathogen. When the number of β-lactamase resistance genes is increased in one plasmid, the transfer of this plasmid can confer broad-spectrum resistance to β-lactams, even if the individual gene confers narrow-spectrum resistance. The present study adds important information about the potential risk of sewage treatment plants as reservoirs and environmental suppliers of AMR genes, contributing to the public health from a One Health perspective.